Insights Into the Therapeutic Effect of Responsive Neurostimulation Assessed With Scalp EEG Recording: A Case Report. Issue 5 (September 2018) - Bruzzone, Maria Jose; Issa, Naoum; Rose, Sandra; Warnke, Peter; Towle, Vernon L.; Tao, James X.; Wu, Shasha
Abstract : Summary: The responsive neurostimulation system (RNS) is the first closed-loop neurostimulator approved as an adjunctive treatment for adults with medically refractory focal epilepsy from no more than two seizure foci. In addition to its therapeutic effect, it provides chronic intracranial EEG recordings, with limited storage capacity. Long-term monitoring with scalp EEG recordings can provide additional information regarding seizure patterns, the efficacy of RNS stimulation in aborting individual seizures, and the net effect of RNS on seizure control. We present a 34-year-old woman with medically intractable right temporoparietal lobe epilepsy who failed two resective epilepsy surgeries and MR-guided laser interstitial thermal therapy (MRgLITT), after which RNS was implanted. Long-term scalp EEG performed 16 months after implantation showed continuous right hemisphere slowing and right temporal sharp waves. In addition, RNS stimulation produced bursts of high-voltage, broad-field, surface-negative activity, which allowed correlation of RNS stimulation with scalp EEG patterns. Twenty-seven seizures were captured. Responsive neurostimulation system stimulation did not abort any of the seizures recorded on the scalp EEG. However, the frequency of seizures doubled after RNS stimulation was discontinued and returned to baseline once it was turned back on. This observation supports the neuromodulation effect of RNS.